Bulk α-alumina embedded tapered fiber as Q-switcher in an erbium-doped fiber laser - Mahdi, Mohd Adzir; Yusoff, Norita Mohd; Liew, Josephine Ying Chyi; Ng, Eng Khoon; Zain, Ahmad Rifqi Md; Alresheedi, Mohammed Thamer; Mayzan, Mohd Zul Hilmi (Institute of Physics Publishing, 2024)
We present bulk alpha-alumina (Al2O3) embedded in a polydimethylsiloxane (PDMS) matrix and deposited on a tapered fiber as a Q-switcher for microsecond pulse generation. The integration of the Al2O3-based saturable absorber (SA) in an erbium-doped fiber laser produced a stable Q-switched regime within a pump power range of 62.0–308.6 mW. The laser achieved a shortest pulse width of 7 microseconds with a repetition rate tunable from 19.17 to 43.24 kHz. Compared with previous Al2O3-SA reports, this work demonstrates significant improvement, delivering pulse energy up to 150.32 nJ and an estimated damage threshold exceeding 6.75 GW/cm2. These results suggest that Al2O3-SA is a promising next-generation light-absorbing material for high-energy photonic devices.